Preliminary clinical evaluation of meningococcal disease and bacterial meningitis by ultrasonic enhancement. Issue 1 (1st January 1998) - Barnes, R A; Jenkins, P; Coakley, W T
Abstract : Antigen detection in the urine and serum may be useful in the diagnosis of suspected meningococcal disease, especially after previous antibiotic treatment. Current test card procedures using commercial agglutination kits are often too insensitive to contribute to diagnosis. Diagnosis of meningococcal disease rose from 37% with the test card procedure to 74% following ultrasonic enhancement.